Assessment of Patient Safety Culture among Nurses at a Tertiary Level Hospital in Kathmandu - Poudel, Sabitra; Aryal, Menuka; Paudel, Narayani (Journal of Karnali Academy of Health Sciences, 2019)
Introduction: Patient safety is a fundamental and critical dimension of quality health care. Globally it is becoming a major challenge in achieving universal health coverage. The challenge is even more serious in Low and Middle Income Countries like Nepal because safety related harm is more in these countries rather than in developed countries. This study aims to assess the patient safety culture among nurses. Methods:  A descriptive cross-sectional study was conducted at Kathmandu Medical College Public Limited to assess the Patient Safety Culture within the organization among nurses. The data was collected using Agency for Health Care Research and Quality (AHRQ) Hospital survey on patient safety culture questionnaire. Mean score was calculated in different dimensions and Mann-Whitney U test was used to assess the association between safety dimension and demographic variables. Result:  Among 12 areas of patient safety, teamwork within units and organizational learning had the highest mean score whereas the lowest reported score was in staffing followed by supervisor’s expectation and action promoting patient safety. While rating the extent of patient safety, 84% of respondents reported it as average in the organization. Study showed significant association of management support, organizational learning and frequency of event reported with age of respondents and overall perception of patient safety and hands-off/transition with working area. Conclusion: Since the patient safety culture is average within organization, attention needs to be paid to make it adequate in all areas of safety.